Reduced Replication Capacity of NL4-3 Recombinant Viruses Encoding Reverse Transcriptase Integrase Sequences From HIV-1 Elite Controllers - Brumme, Zabrina L.; Li, Chun; Miura, Toshiyuki; Sela, Jennifer; Rosato, Pamela C.; Brumme, Chanson J.; Markle, Tristan J.; Martin, Eric; Block, Brian L.; Trocha, Alicja; Kadie, Carl; Allen, Todd M.; et al. (J Acquir Immune Defic Syndr., 2011)
Background Identifying viral and host determinants of HIV-1 elite control may help inform novel therapeutic and/or vaccination strategies. Previously, we observed decreased replication capacity in controller-derived viruses suggesting that fitness consequences of HLA class I-associated escape mutations in Gag may contribute to this phenotype. This study examines whether similar functional defects occur in Pol proteins of elite controllers. Methods Recombinant NL4-3 viruses encoding plasma RNA-derived Reverse Transcriptase (RT)-Integrase sequences from 58 elite controllers and 50 untreated chronic progressors were constructed and replication capacity measured in vitro using a GFP reporter T-cell assay. Sequences were analyzed for drug resistance and HLA-associated viral polymorphisms. Results Controller-derived viruses displayed significantly lower replication capacity compared to those from progressors (p<0.0001). Among controllers, the most attenuated viruses were generated from individuals expressing HLA-B*57 or B*51. In viruses from B*57+ progressors (N=8), a significant inverse correlation was observed between B*57-associated RT-Integrase escape mutations and replication capacity (R=−0.89; p=0.003); a similar trend was observed in B*57+ controller-derived viruses (N=20, R=−0.36; p=0.08). Conclusions HIV-1 Pol function appeared to be compromised in elite controllers. As observed previously for Gag, HLA-associated immune pressure in Pol may contribute to viral attenuation and subsequent control of viremia.